Filozofia wychowania jako filozofia - Walczak, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
In the article the Author analyzes different ways of understanding and practicing the philosophy of education. This analysis leads to the conclusion that methodological status of philosophy of education is indefinite, and this is an important issue that should be considered. The Author proposes to distinguish the pedagogical philosophy of education from the philosophy of education as a philosophy in the strict sense. The purpose of pedagogical reflection is to improve the process of education. The goal of philosophy is to understand the nature and essence of education, therefore it is a purely theoretical purpose. The Author refers to the classical approach of philosophy being love of wisdom, according to which the philosophy is a disinterested contemplation of truth.